Colonização nasofaríngea pelo Streptococcus pneumoniae em crianças portadoras de doença falciforme imunizadas com a vacina pneumocócica conjugada 7-valente - Fonseca, Patricia Belintani Blum [UNIFESP] (2010)
Objectives: To assess the prevalence of nasopharyngeal colonization by Streptococcus pneumoniae in children with sickle cell disease using prophylactic penicillin and immunized with 7-valent pneumococcal conjugate vaccine; to identify risk factors for nasopharyngeal colonization; to assess the resistance profile to penicillin and other antimicrobials and to determine the most frequent serotypes in the nasopharyngeal isolates in children with sickle cell disease and in children from the control group. Methodology: Cross-sectional case-control study. A total of 424 swabs were collected from the nasopharynx in 216 children with sickle cell disease and 109 samples from the control group, both in the age range of 2 to 60 months, in the period between 11/06/2007 and 11/28/2008. Isolation and identification of pneumococcus followed standard procedures. Minimum inhibitory concentration (MIC) for penicillin and ceftriaxone were determined by the E-test method and interpreted according to CLSI 2008 criteria. Serotyping was performed by the Neufeld-Quellung reaction and by Imuno- blot. Results: Prevalence of nasopharyngeal colonization by pneumococcus in the 216 children with sickle cell disease was 17%, and 11% in the control group. The risk factors for increased colonization in children with sickle cell disease were the presence of more than five people in home (p=0.004), daycare/school attendance (p= 0.003) and low prophylaxis compliance (p=0,007). The prevalence of strains with penicillin resistance was 57.5% in patients with sickle cell disease and 25% in the control group, and in regard to ceftriaxone it was 15% and 16.7% respectively. There were no strains resistant to levofloxacin and vancomycin. The most frequently isolated serotype in both groups was NT (strains without polysaccharide capsule). Vaccine serotypes 6B, 14, 19F and 23F were isolated from five colonized children with sickle cell disease (13,5%), four of them with complete immunization for their age. Conclusions: Prevalence of nasopharyngeal colonization by pneumococcus was similar among the groups; although the penicillin prophylaxis decrease colonization, the high prevalence of strains resistant to penicillin among sickle cell disease patients may have been responsible for the similarity in the colonization rate. Prophylactic use of penicillin favored the increased prevalence of resistant strains. Since in the control group the most prevalent strain was also NT, it was not possible to verify the vaccine’s efficacy in decreasing the colonization by the vaccine serotypes.